Regulation of reticulophagy by the N-degron pathway. Issue 2 (1st February 2020) - Ji, Chang Hoon; Kim, Hee Yeon; Heo, Ah Jung; Lee, Min Ju; Park, Daniel Youngjae; Kim, Dong Hyun; Kim, Bo Yeon; Kwon, Yong Tae
ABSTRACT: Cellular homeostasis requires selective autophagic degradation of damaged or defective organelles, including the endoplasmic reticulum (ER). Previous studies have shown that specific ER transmembrane receptors recruit LC3 on autophagic membranes by using LC3-interacting domains. In this study, we showed that the N-degron pathway mediates ubiquitin (Ub)-dependent reticulophagy. During this 2-step process, the ER transmembrane E3 ligase TRIM13 undergoes auto-ubiquitination via lysine 63 (K63) linkage chains and acts as a ligand for the autophagic receptor SQSTM1/p62 (sequestosome 1). In parallel, ER-residing molecular chaperones, such as HSPA5/GRP78/BiP, are relocated to the cytosol and conjugated with the amino acid L-arginine (Arg) at the N-termini by ATE1 (arginyltransferase 1). The resulting N-terminal Arg (Nt-Arg) binds the ZZ domain of SQSTM1, inducing oligomerization of SQSTM1-TRIM13 complexes and facilitating recruitment of LC3 on phagophores to the sites of reticulophagy. We developed small molecule ligands to the SQSTM1 ZZ domain and demonstrate that these chemical mimics of Nt-Arg facilitate reticulophagy and autophagic protein quality control of misfolded aggregates in the ER.